IMPLEMENTASI PEMBELAJARAN MATEMATIKA DENGAN PENDEKATAN MENDALAM MENGGUNAKAN PAPAN INTERAKTIF DIGITAL - Hanif Evendi; Yossie Rosida; Dani Zularfan; Alfian Mubarok (LPPM Institut Ahmad Dahlan Probolinggo, 2026)
Mathematics learning in the Independent Curriculum uses an in-depth approach in the odd semester of the 2025/2026 academic year, focusing on conceptual understanding, critical thinking, and students' reflective abilities. This study aims to describe how Mathematics learning is carried out with an in-depth approach and the challenges faced by teachers at SMP Negeri 4 Kragilan. This study used a qualitative method. Data collection included classroom observations of three Mathematics teachers, as well as collecting documentation of learning tools. Data analysis was carried out using the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. The research findings indicate that the implementation of in-depth learning is in the good category with an average achievement of 85%. Teacher 1 recorded a score of 82%, Teacher 2 recorded 88%, while Teacher 3 recorded 86%. The understanding aspect reached 88%, application 82%, and reflection 81%. Challenges faced were uneven prior knowledge, low participation in group discussions, difficulties with abstract mathematics material, and independent learning and reflection. Teachers address these challenges by simplifying materials, utilizing digital interactive boards to provide contextual examples, using a variety of learning methods, and making reflection a habit at the end of learning sessions.